2019
DOI: 10.1186/s12891-018-2388-9
|View full text |Cite
|
Sign up to set email alerts
|

Knee osteoarthritis patients with more subchondral cysts have altered tibial subchondral bone mineral density

Abstract: BackgroundSubchondral bone cysts are a widely observed, but poorly understood, feature in patients with knee osteoarthritis (OA). Clinical quantitative computed tomography (QCT) has the potential to characterize cysts in vivo but it is unclear which specific cyst parameters (e.g., number, size) are associated with clinical signs of OA, such as disease severity or pain. The objective of this study was to use QCT-based image-processing techniques to characterize subchondral tibial cysts in patients with knee OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
2
21
2
Order By: Relevance
“…The properties and structure of the STB in OA could be characterized by dual X-ray absorptiometry (DXA) [11], X-ray computed tomography (CT) [12], CT arthrography [13], micro-CT (μCT) [14], and magnetic resonance imaging (MRI) [15,16]. Previous studies have reported that knee OA severity, based on histological score [17], Kellgren-Lawrence (K-L) grade [18], cartilage defects, and cartilage thinning, was positively correlated with tibial plateau subchondral bone mineral density (BMD), trabecular bone volume fraction (BV/TV), trabecular number (Tb.N), and trabecular thickness (Tb.Th), suggesting that subchondral bone is closely related to OA severity.…”
Section: Introductionmentioning
confidence: 99%
“…The properties and structure of the STB in OA could be characterized by dual X-ray absorptiometry (DXA) [11], X-ray computed tomography (CT) [12], CT arthrography [13], micro-CT (μCT) [14], and magnetic resonance imaging (MRI) [15,16]. Previous studies have reported that knee OA severity, based on histological score [17], Kellgren-Lawrence (K-L) grade [18], cartilage defects, and cartilage thinning, was positively correlated with tibial plateau subchondral bone mineral density (BMD), trabecular bone volume fraction (BV/TV), trabecular number (Tb.N), and trabecular thickness (Tb.Th), suggesting that subchondral bone is closely related to OA severity.…”
Section: Introductionmentioning
confidence: 99%
“…
Subchondral bone cysts are frequently found in late-stage osteoarthritis. [1][2][3] Cyclic compressive load-bearing or shearloading results in bone marrow lesions due to subchondral damage. [4][5][6] Histologically, these are focal areas of fibrosis, necrosis, microcracks, or microfractures.
…”
mentioning
confidence: 99%
“…In recent years, substantial evidence has shown that subchondral bone and cartilage are a closely related integrated unit and mutually adaptable [ 28 30 ]. In the early stage of KOA, the absorption of subchondral bone is enhanced, and the mechanical strength of the bone is reduced.…”
Section: Discussionmentioning
confidence: 99%